Economic Growth in Indonesia: A Comparative Study of Conventional and Islamic Economic Theories - Assafii, Abdul Rahman; Triana, Nita; Zayyadi, Ahmad; Adliya, I'anatul; Romdhoni, Ahmad (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This article discusses the theory and dynamics of economic growth in Indonesia with a focus on comparative analysis between conventional and Islamic economic approaches. The period studied covers the years 2018 to 2023, during which both economic systems show significant developments in their contribution to national economic growth. Conventional economics, with key indicators such as Gross Domestic Product (GDP) and per capita income, focuses on the accumulation of capital, labour, and technology. In contrast, Islamic economics prioritises the principles of justice, social welfare and the prohibition of usury, which are realised through instruments such as ZISWAF (Zakat, Infaq, Sadaqah and Waqf) and sharia-based finance. Through a descriptive-analytical approach, this article identifies the advantages and challenges of both approaches. Conventional economics offers rapid growth but often faces problems of inequality and social exclusion. On the other hand, Islamic economics contributes to financial inclusion, economic equity and poverty alleviation, although it faces constraints in legal and regulatory infrastructure. The analysis shows that integration between the two approaches can provide a holistic solution for inclusive and sustainable economic growth in Indonesia, and support the achievement of the Sustainable Development Goals (SDGs).